PENERAPAN AKUPRESUR PERIKARDIUM 6 TERHADAP MUAL MUNTAH PADA IBU HAMIL TRIMESTER I - Beril Triana; Prasida Yunita (Universitas Batam, 2023)
Based to WHO, it reaches 12.5% ​​of all pregnancies in the world. Nausea and vomiting causes a decrease in appetite and changes in electrolyte balance which also results in changes in the body's metabolism. Pericardium 6 acupressure point is considered useful for reducing complaints of nausea and vomiting. The aim of the research is to provide midwifery care for pregnant women in a comprehensive and sustainable manner, with management of midwifery care in accordance with midwifery service standards. The midwifery care that is applied is the application of pericardium 6 point acupressure for nausea and vomiting of pregnant women. The type of research used in the preparation of practice reports is descriptive research using the case study method. The research was conducted at the Tanjung Balai Karimun Health Center in March 2023. The subjects were pregnant women by applying pericardial point 6 acupressure. P6 acupressure was carried out by 3 fingers under the wrist in a circular manner, carried out for 7 minutes every morning. After reviewing the case and evaluating the case, there is no gap between theory and practice in the field. This is consistent with the theory that pericardial acupressure can reduce emesis gravidarum.